What is relativity? : an intuitive introduction to Einstein's ideas, and why they matter - Bennett, Jeffrey O. (Columbia University Press, 2014)
It is common knowledge that if the Sun suddenly turned into a black hole, it would suck Earth and the rest of the planets into oblivion. Yet as bestselling author and astrophysicist Jeffrey Bennett points out, black holes don't suck. With that simple idea in hand, Bennett begins an entertaining introduction to Einstein's theories, describing the amazing phenomena readers would actually experience if they took a trip through a black hole. The theory of relativity also gives us the cosmic speed limit of the speed of light, the mind-bending ideas of time dilation and curvature of spac.